ANALISIS PEMASARAN AGROINDUSTRI NATA DE COCO DI KOTA PEKANBARU - Evy Maharani; Susy Edwina; Rani Astuti (Fakultas Pertanian, Universitas Riau, 2018)
Nata de coco is a product of processed agroindustry from coconut water fermented by using Acetobacter microbe. Nata de coco has a promising prospect as it is a worldwide product. This research aimed to identify marketing channel, analyze margin and marketing efficiency of Sari Coco agroindustry in Pekanbaru City. The data used in this research are primary and secondary data. Data analysis method used is margin and marketing efficiency. Sari Coco's marketing research results consist of two channels. Channel I sell directly to consumers who come to the business location to obtain Sari Coco has an efficiency value of 0% with a margin of IDR 0. While the value of marketing efficiency of channel II that is to retailers who are in Sorek Village Pelalawan District is of 0.12% with margin of IDR 7.000 and RCR value of 1.4.strategy, nata de coco, agroindustry, marketing, efficiency